The Implementation of Application-Based Learning Media Canva in Increasing Students' Interest of Class VIII Christian Religious Learning at Marisi Medan Private Middle School - Siringoringo, Widi L.; Munthe, Bangun; Bangun, Bangun (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The purpose of this research is to see how the implementation of learning media based on the Canva application increases students' interest in learning in Christian religious learning in Class VIII SMP Marisi Medan with a total of 26 people. This research uses a descriptive method, while the data analysis carried out by hypothesis research is product moment person correlation and the data collection tool is a questionnaire. From the test results, a correlation (r) of 0.63 was obtained with a determination test of 39.69% and to determine whether the correlation coefficient was significant at the real level (a) = 0.05 then a